Symmetric split Hopkinson compression and tension tests using synchronized electromagnetic stress pulse generators. (December 2018) - Nie, Hailiang; Suo, Tao; Shi, Xiaopeng; Liu, Huifang; Li, Yulong; Zhao, Han
Highlight: Symmetric split Hopkinson compression and tension tests using synchronized electromagnetic stress pulse generators. The measured forces and velocities at the pressure bar/specimen interfaces are indeed identical and simultaneous. Easy control of the synchronism and identity of generated stress pulses by the parallel connection of the stress pulse generators in the LC discharge circuit. The formulas to calculate the stress, strain, and strain rate of the tested specimen in the symmetric test. A novel dynamic loading technique to create the pure Mode I fracture in DCB test. Abstract: This work presents an original impact testing arrangement and its applications using two identical synchronized stress pulses to load symmetrically the specimen sandwiched between the two identical Hopkinson pressure bars. In order to obtain two synchronized stress pulses, two identical electromagnetic stress pulse generators connected to the same LC discharge circuit are used. This symmetric impact loading configuration might be easily interchanged into a compressive as well as a tensile version because of the versatility of the electromagnetic stress pulse generators. In order to validate this apparatus, two materials (copper alloy and aluminum alloy) are tested in compression and in tension using this new experimental setup. The measured forces and velocities at the pressure bar/specimen interfaces are indeed identical and simultaneous. The derived material properties of tested materials are compared with those of the traditional split Hopkinson bars and a good agreement is found. A new symmetric Double Cantilever Beam (DCB) test using this experimental device is also presented. It allows overcoming the difficulties of only one moving side in previous work, which avoids an induced mode II component in a DCB test supposed to be a pure mode I testing.